Evaluation of growth performance and gastro-intestinal parameters on the response of weaned piglets to dietary organic acids - Grecco, Henrique A. T. [UNESP]; Amorim, Alessandro B.; Saleh, Mayra Anton Dib [UNESP]; Tse, Marcos L. P. [UNESP]; Telles, Filipe G. [UNESP]; Miassi, Gabriela M. [UNESP]; Pimenta, Guilherme M. [UNESP]; Berto, Dirlei A. [UNESP] (FapUNIFESP (SciELO), 2018)
Two experiments (E) were carried out to evaluate the effects of fumaric acid and an acidifier blend [composed by calcium formate, calcium lactate and medium-chain fatty acids (capric and caprylic)] in piglet diets containing colistin (40 ppm) or halquinol (120 ppm) on performance, diarrhea incidence (E1), organs relative weight, pH values, intestinal morphometry and microbiota (E2). In E1, 192 and E2, 24 piglets weaned at 21-day-old were randomly assigned to blocks with 2x2 factorial arrangement of treatments [absence or presence of fumaric acid x absence or presence of acidifier blend], six replicates of eight (E1) and one piglet per pen (E2). For E1, the treatments were control (CD): no acidifier product + 40 ppm of colistin, FA: fumaric acid in absence of acidifier blend, AB: acidifier blend in absence of fumaric acid and, AF+AB: presence of fumaric acid and acidifier blend. For E2, the pre-starter I diet were used and the same treatments as E1 evaluated. No treatment effects (P>0.05) were observed on performance, diarrhea incidence (E1), gut pH values and duodenum morphometry of piglets (E2). However, the addition of AB increased (P<0.05) large intestine relative weight and, FA addition decreased (P<0.05) pancreas relative weight, jejunum villi height and, total coliform and E. coli counts in cecum. The inclusion of FA and AB in diets containing colistin or halquinol did not improve performance, although FA exerted an inhibitory effect on cecum microbiota.
Keywords: Acidifiers; Diarrhea; Nutrition; Pig; Weaning